2021
DOI: 10.1021/acscatal.1c02901
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective α-Fluorination and α-Chlorination of N-Acyl Pyrazoles Catalyzed by a Non-C2-Symmetric Chiral-at-Rhodium Catalyst

Abstract: A non-C 2 -symmetric and sterically demanding chiral-at-rhodium catalyst is demonstrated to efficiently catalyze the highly enantioselective α-fluorination [12 examples, up to >99% enantiomeric excess (ee)] and α-chlorination (12 examples, up to 98% ee) of N-acyl pyrazoles in high yields. Based on two sterically distinct cyclometalating ligands, the nonracemic rhodium(III) catalyst can conveniently be accessed in an enantiomerically pure fashion (>99% ee) via an established auxiliary-mediated approach. Compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 67 publications
2
8
0
Order By: Relevance
“…We next tested two new chiral ruthenium catalysts both containing one cyclometalating ligand and a stereogenic metal center (with exclusively achiral ligands). The catalyst Λ- Ru4 , which bears a cyclometalating phenylbenzothiazole ligand and a coordinated 1,10-phenanthroline, provided the flavanone ( R )- 3 in 99% yield and with 87% ee (entry 5), while Λ- Ru5 bearing a cyclometalating phenylpyrazole ligand instead afforded the flavanone ( R )- 3 with the same almost quantitative yield but an improved 94% ee (entry 6). These cyclometalated ruthenium complexes appeared to be highly suitable for the ring-closing C­(sp 3 )–H insertion reaction to yield flavanones.…”
Section: Resultsmentioning
confidence: 99%
“…We next tested two new chiral ruthenium catalysts both containing one cyclometalating ligand and a stereogenic metal center (with exclusively achiral ligands). The catalyst Λ- Ru4 , which bears a cyclometalating phenylbenzothiazole ligand and a coordinated 1,10-phenanthroline, provided the flavanone ( R )- 3 in 99% yield and with 87% ee (entry 5), while Λ- Ru5 bearing a cyclometalating phenylpyrazole ligand instead afforded the flavanone ( R )- 3 with the same almost quantitative yield but an improved 94% ee (entry 6). These cyclometalated ruthenium complexes appeared to be highly suitable for the ring-closing C­(sp 3 )–H insertion reaction to yield flavanones.…”
Section: Resultsmentioning
confidence: 99%
“…Enantioselective carbon–halogen (Cl, Br) bond formations are particularly important due to their potential as synthetic intermediates as well as marine natural products and pharmaceuticals. , Among the various methods available to build carbon–halogen bonds, the enantioselective electrophilic α-halogenation of carbonyl compounds is one of the most common. Over the past few decades, α-halogenation reactions using 1,3-dicarbonyl compounds, aldehydes, and ketones have been well established. However, few reports are available on catalytic enantioselective α-chlorination for carboxylic acid derivatives with p K a values that are relatively high, and hence it has been considered to be challenging to generate enolate species catalytically . In 2001, Lectka et al reported the cinchona alkaloid catalyzed enantioselective chlorination , and bromination , /esterification of acyl chlorides (tandem method, Scheme a).…”
mentioning
confidence: 99%
“…Selectfluor in the presence of a non-C 2 -symmetrical chiral-atrhodium catalyst provided the fluorinated product in high ee values (Scheme 18). 33 The catalytic performance of the non-C 2 -symmetrical rhodium catalysts revealed to be superior to the related C 2 -symmetrical rhodium catalysts.…”
Section: Scheme 12 Metal-catalyzed Enantioselective Fluorination Of ...mentioning
confidence: 95%
“…These less acidic carboxylic acid derivatives, compared to the above mentioned substrates, were engaged in the enantioselective chlorination using trifluoromethanesulfonyl chloride as chlorine source and a non-C 2 -symmetrical chiral-atrhodium catalyst (Scheme 26a). 33 This piece of work followed the -fluorination reported in section 7.9.2.4. N-acyl pyrazoles featuring a -(het)aryl residue provided the chlorinated products in high ee values while the -propyl substrates could not be converted.…”
Section: Scheme 25 Metal-catalyzed Enantioselective Chlorination Of ...mentioning
confidence: 99%